A new internet tool to report peritoneal malignancy extent. PeRitOneal MalIgnancy Stage Evaluation (PROMISE) application. Issue 6 (June 2016) - Villeneuve, L.; Thivolet, A.; Bakrin, N.; Mohamed, F.; Isaac, S.; Valette, P.-J.; Glehen, O.; Rousset, P.; ,
Abstract: Based on the importance of assessing the true extent of peritoneal disease, PeRitOneal MalIgnancy Stage Evaluation (PROMISE) internet application (www.e-promise.org ) has been developed to facilitate tabulation and automatically calculate surgically validated peritoneal cancer index (PCI), and other surgically validated scores as Gilly score, simplified peritoneal cancer index (SPCI), Fagotti and Fagotti-modified scores. This application offers computer-assistance to produce simple, quick but precise and standardized pre, intra and postoperative reports of the extent of peritoneal metastases and may help specialized and non-specialized institutions in their current practice but also facilitate research and multicentre studies on peritoneal surface malignancies.